Incipient Domestication Processes in Multicultural Contexts: A Case Study of Urban Parks in San Carlos de Bariloche (Argentina) - Betancurt, Romina; Rovere, Adriana E.; Ladio, Ana H. (Frontiers in Ecology and Evolution, 2017)
Up to now, the processes of domestication of urban landscapes have been little studied. The public green spaces in the city of Bariloche, an enclave with growing urbanization which lies within the Andino Norpatagonica Biosphere Reserve, offer an opportunity to evaluate cultural molding of the environment. We analyzed different management methods of woody species, both in situ and ex situ, in parks located in sectors with different environmental, socioeconomic, size, age and administration characteristics. Our hypotheses were: (1) Species richness will be higher for exotic plants, in accordance with global patterns of ornamental species selection. (2) Species richness and type of management practice will vary according to the kind of environment, the socioeconomic profile of the neighborhood, the age and size of the park, and type of administration (bottom-up or top-down). (3) Bottom-up park administration will lead to a different landscape than top-down administration. Thirty randomly selected parks of both local council and neighborhood administration and varying environmental and socioeconomic conditions were examined and the composition of their woody species identified. In addition, semi-structured and free interviews were carried out with those responsible for park management, both in situ (tolerance, enhancement, protection) and ex situ (sowing, use of cuttings or transplanting). In accordance with our hypothesis, the processes of domestication of the urban landscape show a tendency towards an anthropized diversity of 130 species, mainly exotic in origin (72%), and principally from the Holarctic region (67%). However, multinomial logistic analysis revealed that in parks under neighborhood administration tolerance of native species is higher (13 times) than in parks administrated by the local council. Species richness increases along an environmental and socioeconomic gradient, and with the age of parks, but does not vary with size. We conclude that urban parks are constructed cultural niches which, as in an agroforestry system, are scenarios which reveal processes of incipient domestication that reflect different cosmovisions and drivers typical of multicultural contexts.